2022
DOI: 10.3390/ijms23158401
|View full text |Cite
|
Sign up to set email alerts
|

Long-Chain Acyl-CoA Synthetases Promote Poplar Resistance to Abiotic Stress by Regulating Long-Chain Fatty Acid Biosynthesis

Abstract: Long-chain acyl-CoA synthetases (LACSs) catalyze fatty acids (FAs) to form fatty acyl-CoA thioesters, which play essential roles in FA and lipid metabolisms and cuticle wax biosynthesis. Although LACSs from Arabidopsis have been intensively studied, the characterization and function of LACSs from poplar are unexplored. Here, 10 poplar PtLACS genes were identified from the poplar genome and distributed to eight chromosomes. A phylogenetic tree indicated that PtLACSs are sorted into six clades. Collinearity anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…evm.model.CTG_1914.20, evm.model.CTG_2264.34, and evm.model. CTG_2192.44 have been identified to play significant roles in salt tolerance (Jia et al, 2023;Li et al, 2015;Wei et al, 2022). Additionally, the homologous genes of evm.model.CTG_2192.44 in rice have been linked to flooding tolerance (He et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…evm.model.CTG_1914.20, evm.model.CTG_2264.34, and evm.model. CTG_2192.44 have been identified to play significant roles in salt tolerance (Jia et al, 2023;Li et al, 2015;Wei et al, 2022). Additionally, the homologous genes of evm.model.CTG_2192.44 in rice have been linked to flooding tolerance (He et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the homologous genes of evm.model.CTG_1235.41 and evm.model.CTG_1914.20 have been found to be involved in responses to drought stress (Ni et al., 2021; Xue et al., 2017). Similarly, the homologous genes of evm.model.CTG_1914.20 , evm.model.CTG_2264.34 , and evm.model.CTG_2192.44 have been identified to play significant roles in salt tolerance (Jia et al., 2023; Li et al., 2015; Wei et al., 2022). Additionally, the homologous genes of evm.model.CTG_2192.44 in rice have been linked to flooding tolerance (He et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that most of C18 fatty acids and VLCFAs (i.e., 12-oxo-5,8,10,14-eicosatetraenoic acid, 13 S -hydroperoxy-9 Z ,11 E -octadecadienoic acid, 15-oxo-5 Z ,8 Z ,11 Z ,13 E -eicosatetraenoic acid, and 2 R -hydroxy-9 Z ,12 Z ,15 Z -octadecatrienoic acid) were markedly downregulated under OPDA treatment ( Figure 2 ). The carbon chain length, unsaturation, and head structure polarity of VLCFAs make them extremely diverse in structure and function and play a key role in transmembrane transport, cell division and differentiation, energy storage, resistance to stress, and other physiological processes [ 42 , 44 ]. Our result showed that lots of markedly upregulated or downregulated family genes (i.e., 3-ketoacyl-CoA synthase, 3-ketoacyl-CoA thiolase, and long-chain acyl-CoA synthetase) involved in phospholipids biosynthesis in P. nutans ( Figure 6 and Table S2 ).…”
Section: Discussionmentioning
confidence: 99%